The Cambridge companion to the cistercian order. - Bruun, Mette Birkedal (Cambridge Cambridge university press, 2013)
"This volume presents the composite character of the Cistercian Order in its unity and diversity, detailing the white monks' history from the Middle Ages to the present day. It charts the geographical spread of the Order from Burgundy to the peripheries of medieval Europe, examining key topics such as convents, liturgy, art, agriculture, spiritual life and education, providing an insight into Bernard of Clairvaux's life, work and sense of self, as well as the lives of other key Cistercian figures. This Companion offers an accessible synthesis of contemporary scholarship on the Order's interaction with the extramural world and its participation in, and contribution to, the cultural, economical and political climate of medieval Europe and beyond. The discussion contributes to the history of religious orders, and will be useful to those studying the twelfth-century renaissance, the apostolic movement and the role of religious life in medieval society"--
Machine generated contents note: Introduction: withdrawal and engagement Mette Birkedal Bruun and Emilia Jamroziak; Part I. History: 1. Foundation and twelfth century Martha G. Newman; 2. The Cistercian Order, 1200-1600 Peter King; 3. The Cistercian Order since 1600 Michael Casey; Part II. Structure and Materiality: 4. Cistercian centres and peripheries Emilia Jamroziak; 5. The Cistercian community James France; 6. Cistercian constitutions and the General Chapter Brian Patrick McGuire; 7. Cistercian nuns Elizabeth Freeman; 8. Cistercian agriculture and economies Constance Hoffman Berman; 9. Cistercian art Diane J. Reilly; 10. Cistercian libraries and scriptoria David N. Bell; 11. Cistercian architecture or architecture of the Cistercians? Thomas Coomans; Part III. Religious Mentality: 12. Bernard of Clairvaux: his first and greatest miracle was himself Christopher Holdsworth; 13. Bernard of Clairvaux: work and self M. B. Pranger; 14. Early Cistercian writers E. Rozanne Elder; 15. The spiritual teaching of the early Cistercians Bernard McGinn; 16. Cistercians in dialogue: bringing the world into the monastery Wim Verbaal; 17. Cistercian preaching Beverly Mayne Kienzle; 18. Cistercian liturgy Nicolas Bell.
Keywords: Cistercians; 271.12 <03> -- Cisterciënzers. Bernardijnen--Naslagwerken. Referentiewerken